1993
DOI: 10.1128/jb.175.10.3224-3227.1993
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Mycoplasma hominis adhesion

Abstract: The high concentrations of sulfated glycolipids in the human endometrium (6) and in mammalian male germ cells (10) suggest an advantage for organisms that can use these glycolipids as receptors. Lingwood and coworkers recently found that M. hominis binds to 2 ,ug of sulfogalactoglycerolipid and sulfogalactosylceramide, or sulfatide, on thin-layer plates (7). However, it was not demonstrated that this attachment is a specific adhesin-receptor interaction rather than some form of nonspecific, perhaps ionic, bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Other studies have reported the same receptor binding specificity for M. pneumoniae (Krivan et al, 1988) and confirmed the glycolipid binding specificity of M . homznis (Olson and Gilbert, 1993). Sulfoglycolipids were recently demonstrated as receptors for M. hyopneumoniae (Zhang et al, 1994a,b) as we would predict from our present studies.…”
Section: Immunoelectron Microscopysupporting
confidence: 87%
See 1 more Smart Citation
“…Other studies have reported the same receptor binding specificity for M. pneumoniae (Krivan et al, 1988) and confirmed the glycolipid binding specificity of M . homznis (Olson and Gilbert, 1993). Sulfoglycolipids were recently demonstrated as receptors for M. hyopneumoniae (Zhang et al, 1994a,b) as we would predict from our present studies.…”
Section: Immunoelectron Microscopysupporting
confidence: 87%
“…Four speciesspecific mycoplasmas associated with infertility bind to SGC and SGG (Lingwood et al, 1990a,b). Other investi- gators have demonstrated a similar glycolipid binding specificity for Mycoplasma pneumoniae (Krivan et al, 1988) and sulfoglycolipids were confirmed as the only receptor species for Mycoplasma hominis (Olson and Gilbert, 1993). Mycoplasma hyopneumoniae was recently shown to bind SGC and sulfoglycolipids found to mediate the attachment of this organism to ciliated respiratory epithelium (Zhang et al, 1994a).…”
mentioning
confidence: 84%
“…It is worthy to note that the apical microvillar border and cilia of the epithelium express the sialoglycoconjugate-type receptors, thus allowing the selective attachment of M. pneumoniae to the ciliated cells [Krivan et al, 1988Roberts, D.D. et al, 1989;Olson & Gilbert, 1993;Rottem & Naot, 1998]. Cytadhered M. pneumoniae is able to cause damage through generation of reactive oxygen species (ROS), which act in concert with host's endogenous ROS to induce oxidative stress.…”
Section: Pathogenesismentioning
confidence: 99%
“…It is likely that surface proteins and lipids that facilitate the adhesion process will have an effect on invasion (Krivan et al, 1989;Olson and Gilbert, 1993;Zhang et al, 1994;Athamna et al, 1996). It has been shown that bacterial and viral invasion is based on the ability of several pathogens to attach to fibronectin or sulphated polysaccharides (Christensen et al, 2001).…”
Section: Tablementioning
confidence: 99%